(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article examines the prospects for the development of agritourism in Bustonliq District, one of the most attractive natural and recreational regions of Uzbekistan. The study highlights the significance of agritourism in supporting rural economic growth, increasing employment opportunities, preserving national traditions, and promoting sustainable tourism. The article also analyzes the natural resources, agricultural potential, and tourism infrastructure of Bustonliq District. Particular attention is given to the opportunities and challenges associated with the development of agritourism in the region. Recommendations for improving infrastructure, attracting investments, and enhancing local participation are provided. The research emphasizes that agritourism can become an important factor in strengthening the socio-economic development of rural areas while simultaneously promoting ecological sustainability and cultural heritage.